2021
DOI: 10.1111/jcpe.13546
|View full text |Cite
|
Sign up to set email alerts
|

Differences in platelet‐rich plasma composition influence bone healing

Abstract: Aim: Platelet-rich plasma (PRP) is an autologous blood-derived material that has been used to enhance bone regeneration. Clinical studies, however, reported inconsistent outcomes. This study aimed to assess the effect of changes in leucocyte and PRP (L-PRP) composition on bone defect healing.Materials and Methods: L-PRPs were prepared using different centrifugation methods and their regenerative potential was assessed in an in-vivo rat model. Bilateral critical-size tibial bone defects were created and filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…The cellular behavior of macrophages is of much concern and a dynamic balance between immune response and regenerated signal during inflammatory phase is the prerequisite for the orderly development of the subsequent proliferation and remodeling phases. It has also been previously reported that activated PLTs could modulate macrophage polarization in vitro and in vivo [ 59 ]. Raw264.7 macrophages were co-cultured with negative control and 3D printed biolayer skin substitutes.…”
Section: Resultsmentioning
confidence: 92%
“…The cellular behavior of macrophages is of much concern and a dynamic balance between immune response and regenerated signal during inflammatory phase is the prerequisite for the orderly development of the subsequent proliferation and remodeling phases. It has also been previously reported that activated PLTs could modulate macrophage polarization in vitro and in vivo [ 59 ]. Raw264.7 macrophages were co-cultured with negative control and 3D printed biolayer skin substitutes.…”
Section: Resultsmentioning
confidence: 92%
“…The elemental composition of PVRP can be measured by inductively coupled plasma optical emission spectrometry [ 102 ]. Various metabolites in PVRP samples can be determined by ion-parallel liquid chromatography (LC) and mass spectrometry (MS) or gas chromatography (GC) and MS [ 102 ], or by electrochemical sensors [ 103 ]. Hormones can be determined by liquid chromatography-electrospray ionization tandem mass spectrometry (LC-MS /MS) [ 103 , 104 ].…”
Section: Characterization Of Pvrp Composition and Methodological Appr...mentioning
confidence: 99%
“…Hayvanlar rastgele 4 gruba ayrılmıştır. Laboratuvarda, oda sıcaklığında (25±3 °C), sabit nemli ortamda (55±5 %), gece gündüz periyodunda 3 hafta [14,15] boyunca standart ticari sıçan besini (Bayramoğlu Yem, Erzurum, Türkiye) ile beslenmişlerdir. Besin ve suya ulaşım konusunda herhangi bir kısıtlama yapılmamıştır.…”
Section: Hayvanlar (Animals)unclassified